The potential of contract document as part of occupational safety and health management system - Sulaiman, K.; Sulaiman, R.; Saleh, H.; Hashim, H.A. (2008)
Construction site is dangerous by its nature and are prone to accidents. Extensive efforts have previously been taken in order to minimise its risk. There was a major change in legislation and regulations to OSH with the introduction of Malaysian Occupational Safety and Health Act (OSHA) 1994 by the government. However, it seems that the actions undertaken are still unsatisfactorily which statistic data shows little improvement in the number of accidents and fatalities. The construction activities need to be carried out in accordance to OSH best practice to avoid injuries and large significant financial loss. It is believed that these scenarios can be improved if the overall project cost and monitoring system can be embedded in the contract document. The aim of this research is to provide standard item for OSH requirements in Malaysian procurement documents for construction processes. The objectives are to propose guideline and detail requirements of OSH element for the inclusion of OSH component in planning and preparation of Tender Document that align with the requirement of Malaysian Public Works Department. This research will be carried out in collaboration of the industry, clients and construction professional.